Pregnant women's experiences of social roles: An ethnophenomenological study - Fatemeh Erfanian Arghavanian; Robab Latifnejad Roudsari; Abbas Heydari; Mohsen Noghani Dokht Bahmani (Wolters Kluwer Medknow Publications, 2020)
Background: The role of women and men is changing across the world, and women, including pregnant women, are adopting newer roles in traditional societies like Iran. This study aimed to explore the meaning of pregnant women's experiences regarding their social roles in the sociocultural context of Iran. Materials and Methods: This study was carried out using an ethnophenomenological approach. Participants included 16 pregnant women who attended health centers, hospitals, and private obstetric clinics in Mashhad, Iran, between 2016 and 2017 and were selected based on purposive sampling. In-depth semistructured interviews, vignette interviews, participant observations, and field notes were used to collect data. To analyze data, six-step van Manen's (1997) descriptive-interpretive phenomenological approach was used. Results: Through data analysis, the overarching theme of "selection, management, and adjustment of various roles to play social roles" was emerged. This was consisted of four themes: "Mother's perspective regarding out-of-home employment, incompatibility between pregnancy and social roles, mother's management strategies to play different roles, and husband's authority regarding mother's employment." Conclusions: The consequence of reciprocal endeavors of pregnant women along with their husbands as well as their work environment expectations tends to selection, management, and adjustment of feminine roles. Since the employment of pregnant women leads to their more physical and psychological involvement, not only the problems of working women but also the expectations and rules of the workplaces as well as the requests of their husbands should be taken into account.